Comparative Analysis of Sensitive Space Technology Regulations in Asean Countries - Siregar, Naek; Syofyan, Ahmad; Aida, Melly; Kyrieleison, Eunike Christine (Faculty of Law Universitas Lampung, 2024)
Space technology has rapidly evolved due to technological advancements, emphasizing the need for regulatory attention. This paper examines the regulation of sensitive space technology across ASEAN countries through a comparative analysis. Sensitive space technology, a high-stakes field crucial for conducting space activities, requires regulation due to the boundless nature of space. Typically, the regulation of space activities is established within international law, while specific national laws govern these activities in countries actively engaged in the space sector. The research adopts a descriptive qualitative methodology, utilizing literature reviews as the primary data source. This research aims to explore and compare the regulatory frameworks for sensitive space technology in ASEAN countries. This analysis could serve as a guide or benchmark for Indonesia as it develops national regulations on sensitive space technology. The findings reveal that Indonesia has enacted a Space Act dedicated to the space sector. Malaysia similarly regulates its space activities through a Space Act and accompanying Space Regulations. While lacking a specific law for sensitive space technology, Singapore manages these activities under existing legislative frameworks.